Strategic Imperatives of Business Career of Employees of the Russian Banks - SOTNIKOV, Nikita; SOTNIKOVA, Svetlana; MIKHAILOVA, Elena; NEKHAEV, Andrei (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2019)
The purpose of the research is to develop the organizational and economic foundations of the business career of banking personnel as a mechanism for improving competitive positions in the labor market: (a) to identify the determinants of business career allowing to achieve a higher level of competition on the labor market in changing conditions; (b) to analyze the various strategic alternatives of business career by building two-dimensional matrixes that allow to estimate the prospects of a particular method of positioning bank personnel on the labor market. The research methodology is based on the theoretical analysis of the results of scientific works, which presents the main provisions of the mechanism of business career. The statistical data of the all-Russian statistical reporting, analytical reviews, statistical reports and primary personnel documents of commercial banks, regulatory documents governing activities in the banking sector of the economy, information of periodicals and the global Internet information system, the results of the questionnaire survey of banking employees carried out by the authors (N=1961) were the research information and empirical base. The research was conducted according to quota multistage sampling sample (basic features: organizational strategy, functional responsibilities of the employee and his work experience in the banking organization). The business career of staff of 15 federal and regional banks, listed on the Russian market for eight years, is analyzed in terms of content. The results of the research show that the type and intensity of a business career determine the mechanisms of localization and approval of the competitive advantage of both the employee and the banking organization in the market situation. The knowledge of business career has allowed us to identify the presence of a socio-economic conflict between professional career and organizational (intra-and inter-organizational). The ways of conflict solution about business career generate strategic alternatives of the interaction professional and organizational types of career, aimed to maintaining and increasing the competitiveness of human resources of the banking organization